Feiras municipais como alternativa de comercialização para agricultores familiares - Verano, Thiago de Carvalho (2019)
In the last two decades, there have been important advances in understanding the role of alternative marketing channels for family farmers, given to the growing limitations of conventional food supply chains. But there is still a lack of quantitative analysis on the relevance of alternative market channels, as well as the qualitative understanding of its operation as a means to enhance its promotion. Among the various modalities of alternative marketing channels, farmers’ markets are the most accessed by Brazilian family farmers. This study aims to assess to what extent and in what way farmers’ markets in the state of Goiás represent an alternative for productive inclusion of family farmers. The results reveal that 88% of the studied municipalities have weekly farmers’ markets, 67.16% of them have effective participation of family farmers and 30 municipalities have exclusive markets of family farmers. Statistically, it was concluded that the presence of middlemen inhibits the protagonism of family farmers and that the socio-economic dynamism of farmers’ markets influences the creation of public policies. In Goiás, 10.17% of the farmers’ markets offer opportunities for socio-productive inclusion of family farmers, strengthen short marketing channels, and function as an alternative to the agro- industrial system. These fairs are characterized by being organized by associations of family farmers, by being based on relationships of trust between farmers and local consumers, by having solidary relations between the participants and by acting as catalysts for new transactions between farmers and different markets. Despite the potential represented by the fairs analyzed, this study reveals that, on average, 10.41% of the family farmers in the studied municipalities take part in the municipal farmers’ markets. It is fundamental to promote actions to support these markets given to their role in the inclusion of family farmers in short channels. This study presents the fundamental aspects to be considered in possible policies for the promotion of municipal fairs of the producer.